Music and sustainability: An educational proposal - Franco Pistono (Pensa MultiMedia, 2022)
Sustainability education appears within civic education at school, from September 2020. How to use music to face this interdisciplinary path? Which are the reasons why music is a good ally? With a look at an ongoing project, an invitation to reflect on the usefulness of an approach close to the needs and desires of children in the classrooms.